KEBIJAKAN DAN PENERAPAN DIGITAL KESEHATAN DI RSIJ CEMPAKA PUTIH : TINJAUAN DESKRIPTIF - Wahyuni, Rupi Sri; Roesmayanti, Dewi; Sumiyati, Sumiyati; Imam Santiko, Imam Santiko (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
Social Health Insurance or Jaminan Kesehatan Nasional (JKN) program in Indonesia has started on January 1, 2014. In order for the JKN program to be implemented properly, BPJS Kesehatan as the organizer collaborates with FKTP and FKTL. RSIJ Cempaka Putih is one of the FKTL that provides services to BPJS patients. As an implication of the services that have been provided to BPJS patients, RSIJCP makes payment claims that are submitted in accordance with the terms and conditions of BPJS.In relation to the work activities of the patient's disease coding process, there are two processes, namely the process of providing a diagnosis by a doctor with freetext and then recording by a coder according to the ICD X diagnosis standardization and ICD 9cm medical procedure. This diagnosis data is then summarized as Claim data. The continued formation of patient diagnoses and coding that is not optimal has prompted us to conduct research.The research was conducted at RSIJ Cempaka Putih using a descriptive review method and focused on the Implementation of the RME Application. The decision to implement RME as the main tool is considered to be able to accelerate the claim process to BPJS.Keywords : Electronic Medical Record, BPJS claim, BPJS coding, BPJS claim diagnosis, prosedur klaim